The implementation of algorithm of ranking search result in information system of University library - Андрухів, Андрій Ігорович (Technology audit and production reserves, 2015)
This paper describes the implementation of the algorithm of ranking search results of the user in informational and search system of library. Today, in Ukraine almost no university libraries, that aren’t computerized, at least partially. Libraries offer a range of remote services for their users – e-catalog and specialized e-services. If these services are provided by web means then access to them in most cases is anonymous. Today, libraries have large databases that describe millions of books, magazines and newspapers. If the user does not clearly imagine that he searches, then deal in such large arrays is very difficult. Therefore, in addition to specific features of information system that are used to refine the search query, an important element is the function of governing the presentation of search results - ranking. Implementation of ranking algorithms in the work of library information systems allow users to minimize the time required to find and organize information search based on qualitative criteria. In scientific and technical library of the National University "Lviv Polytechnic" was developed specialized information system that allows you to create a list of books for students. The proposed ranking algorithm was incorporated in the work of the system. In the opinion of users it is greatly improved process for selecting literature for the study of academic disciplines, if literature, recommended by the teacher, doesn’t fit for some reasons